The value of sequential bone marrow biopsy and laparotomy and splenectomy in a series of 127 consecutive untreated patients with non-Hodgkin's lymphoma. - Rosenberg, S. A. (Nature Publishing Group, 1975)
The information derived from sequential routine bone marrow biopsies and exploratory laparotomy with splenectomy in 127 consecutive untreated protocol patients with malignant lymphomata other than Hodgkin's disease is reviewed. Of the 61 patients with diffuse lymphomata, 36% changed stage after these diagnostic procedures, usually to a more advanced stage. Of the 66 patients with nodular lymphomata, 62% had a change in stage, almost all to more advanced stages, usually as a result of bone marrow biopsy. The correlation of pathological stages to clinical stages is presented for each of the Rappaport classification subgroups and for several age groups. The precise indications for exploratory laparotomy with splenectomy cannot yet be defined. These will have to await the results of current clinical trials, which may reveal to what degree an improvement in therapeutic results has been achieved as a result of a better knowledge of the extent of disease.